Giving Presentations : Expert Solutions to Everyday Challenges ; Know your Audience, Plan for Visuals, Overcome Fears, Rehearse Effectively - Morgan, Nick (Boston, Mass Harvard Business Scholl Press, 2007)
Making persuasive presentations isn't just a matter of charisma and fancy charts: it requires concrete skills that are vital to keeping your audience engaged and involved. This handy guide contains key information on how to customize your presentations to keep people focused and produce the results you want.
Include Notes and Illustrations
Keywords: Business presentations